Oscar Wilde in America : the interviews - Wilde, Oscar, 1854-1900; Hofer, Matthew; Scharnhorst, Gary (University of Illinois Press, 2010)
"This comprehensive and authoritative collection of Oscar Wilde's American interviews affords readers a fresh look at the making of a literary legend. Better known in 1882 as a cultural icon than a serious writer (at twenty-six years old, he had by then published just one volume of poems), Wilde was brought to North America for a major lecture tour on Aestheticism and the decorative arts that was organized to publicize a touring opera, Gilbert and Sullivan's Patience, which lampooned him and satirized the Aesthetic "movement" he had been imported to represent." "In this year-long series of broadly distributed and eagerly read newspaper interviews, Wilde excelled as a master of self-promotion. He visited major cities from New York to San Francisco but also small railroad towns along the way, granting interviews to newspapers wherever asked. With characteristic aplomb, he adopted the role as the ambassador of Aestheticism, and reporters noted that he was dressed for the part. He wooed and flattered his hosts everywhere, pronouncing Miss Alsatia Allen of Montgomery, Alabama, the most beautiful young lady he had seen in the United States, adding, "This is a remark, my dear fellow, I supposed I have made of some lady in every city I have visited in this country. It could be appropriately made. American women are very beautiful.""